Analysis of Tawangsari River Water Quality Using the Pollution Index Method in Sidoarjo Regency, Indonesia, during the 2024 Observation Period - Pratama Sandi Alala; Cahya Bagus Syah; Ayu Setyaning Sayekti Poesoko (Institut Teknologi Adhi Tama Surabaya, 2026)
River water quality analysis is a fundamental component of environmental management, particularly for rivers with the potential to serve as raw water sources. The Tawangsari River is influenced by domestic activities and surrounding land use, which may contribute to gradual water quality degradation. This study aims to assess the water quality status of the Tawangsari River using the Pollution Index (PI) method. Water samples were collected at three monitoring points representing upstream, middle, and downstream river segments. Key water quality parameters analyzed included pH, turbidity, Total Dissolved Solids (TDS), Total Suspended Solids (TSS), Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), and Chemical Oxygen Demand (COD). The results indicate that the Pollution Index values classify the Tawangsari River as lightly polluted to moderately polluted, with the highest PI value observed at the middle segment of the river. Among the evaluated parameters, dissolved oxygen was identified as the dominant factor influencing the Pollution Index values. It should be noted that the assessment was conducted using a limited number of monitoring points within a single observation period. Despite these limitations, the findings provide a reliable overview of the current water quality status of the Tawangsari River and demonstrate the applicability of the Pollution Index method as a practical tool for river water quality assessment and management planning. Keywords: pollution index; river water quality; dissolved oxygen; environmental monitoring; water quality status